O01-2 Psychosocial working conditions and burnout among german employees: initial results from a population based cohort study. (1st September 2016) - Rose, Uwe; Müller, Grit; Freude, Gabriele
Abstract : Introduction: A major deficit in studies on occupational burnout is the lack of population based samples not restricted to professions in the social services or health care system. The same limitation applies to studies on psychosocial working conditions and mental health outcomes, which together comprise the focus of the German Study on Mental Health at Work (S-MGA). The study entails a registry based sample of German employees subject to social security contributions. This presentation gives an overview of the distribution of burnout within the population and its associations with psychosocial working conditions. Method: The sampling frame is defined by all German employees subject to social security contributions and born between 1951 and 1980. The sample consists of 4511 survey participants, of whom 4182 were engaged in full- or part-time employment at the time of interview. Psychosocial working conditions were assessed by a computer assisted personal interview (CAPI). Five working conditions were selected on basis of a previous review. For the statistical analysis all scales are transformed into quartiles. Occupational burnout is assessed by the exhaustion scale of the Oldenburg-Burnout-Inventory (OLBI) using a paper and pencil questionnaire. Cases of burnout are defined by a score of ≥3 (range: 1–4). Results: The prevalence for burnout within this population based survey is 10% for male and 11% for female respondents. The strongest increase of burnout is associated with quantitative demands: the prevalence increases from 3% within the first quartile to 23% within the fourth quartile. Also the remaining COPSOQ-scales are associated with Burnout. Discussion: The current analysis was motivated by findings from international longitudinal studies. The results for this representative sample offers evidence that these findings are applicable to German employees. Furthermore, there are some indications for non-linear aspects in the association between burnout and psychosocial working conditions.